IMPLEMENTASI METODE RABIN KARP PADA APLIKASI PENGECEKAN KEMIRIPAN JUDUL TUGAS AKHIR (Studi Kasus: Jurusan Teknik Informatika Politala) - Novia, Risda; Prastyaningsih, Yunita; Rhomadhona, Herfia (ScientiCO : Computer Science and Informatics Journal, 2021)
Checking the similarity of Final Project (TA) titles can be done by building a similarity detection application and implementing methods to determine the similarity of these TA titles. The method used is the Rabin Karp method, which is a word search method that searches for a pattern in the form of a substring using the hash. The data used in this study are student data and data on the 2016-2018 academic year of the Informatics Engineering Department at Tanah Laut State Polytechnic. The results of the similarity experiment can be divided into 3 (three) parts, namely not similar, somewhat similar, and very similar. It is said to be not similar if the percentage of the equation is 0% -20% as happened in k-gram 6 to k-gram 10. While it is somewhat similar if the percentage is between 21%-55% as seen in k-gram 3, k- gram 4, and k-gram 5. For very similar categories based on the percentage above 56% seen in k-gram 1 and k-gram 2. So it can be concluded that the more or greater the value of k-grams, the smaller the percentage results obtained, on the contrary, if the smaller the value of k-grams, the higher the percentage value.